RNA-Sequencing in Resistant (QL3) and Susceptible (Theis) Sorghum Cultivars Inoculated With Johnsongrass Isolates of Colletotrichum sublineola - Natarajan, Purushothaman; Ahn, Ezekiel; Reddy, Umesh K.; Perumal, Ramasamy; Prom, Louis K.; Magill, Clint (Frontiers in Genetics, 2021)
Gene expression was analyzed at 0- and 24-hours post-inoculation of two inbred sorghum cultivars known to differ in response to inoculation with Colletotrichum sublineola, the fungal pathogen that causes anthracnose. QL3 is reported to have quantitative resistance while Theis is susceptible to most pathotypes of the pathogen; RNASeq identified over 3,000 specific genes in both cultivars as showing significant changes in expression following inoculation; in all but one gene, the changes in QL3 and Thies were in the same direction. Many other genes showed significant changes in only one of the two cultivars. Overall, more genes were down-regulated than up-regulated. Differences in changes in expression levels of a few genes suggested potential roles for the difference in disease response between QL3 and Theis, but did not identify known resistance genes. Gene ontology and pathway enrichment analysis identified upregulation of 23 transcription factor encoding genes as well as genes involved in the production of secondary metabolites, which are part of a typical host defense reaction.